PENGARUH DIGITAL MARKETING TERHADAP VOLUME PENJUALAN ROTI O - Nentyn Aprilia Yonita; Jumriah Basri (Paser Institute Management and Busines, 2025)
The very rapid development of technology in today’s digital era has caused a change in mondset from conventional marketing to digital marketing to reach customer more quickly and flexibly. Researchers conducted this research with the aim of identifying whether or not there is an influence of digital marketing on increasing sales volume for Roti O products. The quantitative approach method in this research uses descriptive verification research. Data was obtained from 96 respondents who are cunsumers of Roti O products. The conclusion of this research shows that digital marketing has a positive and significant influence of the sales volume of Roti O products, based on the t-calculated value of 8,015 which is greater than the t-table value of 1,661.